2015
DOI: 10.1098/rspb.2015.0834
|View full text |Cite
|
Sign up to set email alerts
|

When and how did the terrestrial mid-Permian mass extinction occur? Evidence from the tetrapod record of the Karoo Basin, South Africa

Abstract: A mid-Permian (Guadalupian epoch) extinction event at approximately 260 Ma has been mooted for two decades. This is based primarily on invertebrate biostratigraphy of Guadalupian -Lopingian marine carbonate platforms in southern China, which are temporally constrained by correlation to the associated Emeishan Large Igneous Province (LIP). Despite attempts to identify a similar biodiversity crisis in the terrestrial realm, the low resolution of mid-Permian tetrapod biostratigraphy and a lack of robust geochrono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
132
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(137 citation statements)
references
References 35 publications
5
132
0
Order By: Relevance
“…This climatic shift is possibly related to that of the upper portion of the Alcotas formation in the Iberian Basin (De la Horra et al, 2012) and also to the climatic shift documented in the early late Permian of northern Pangaea (Retallack et al, 2006;Roscher and Schneider, 2006;Słowakiewicz et al, 2009). This may imply that the lower/upper URU boundary could be correlated with the middle-late Capitanian (around the middle Permian extinction event) (Retallack et al, 2006;Sheldon et al, 2014;Day et al, 2015). Nevertheless, the lower/upper URU boundary possibly represents a paraconformity or sedimentary hiatus (i.e., long periods of exposition and development of levels with large nodules; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This climatic shift is possibly related to that of the upper portion of the Alcotas formation in the Iberian Basin (De la Horra et al, 2012) and also to the climatic shift documented in the early late Permian of northern Pangaea (Retallack et al, 2006;Roscher and Schneider, 2006;Słowakiewicz et al, 2009). This may imply that the lower/upper URU boundary could be correlated with the middle-late Capitanian (around the middle Permian extinction event) (Retallack et al, 2006;Sheldon et al, 2014;Day et al, 2015). Nevertheless, the lower/upper URU boundary possibly represents a paraconformity or sedimentary hiatus (i.e., long periods of exposition and development of levels with large nodules; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1) represents an extensive depositional record of Pennsylvanian-early Jurassic fossiliferous sedimentary (Rubidge et al, 1999) rocks that have been critical for understanding the rate of vertebrate turnovers for continental extinction events during the End-Guadalupian and across the Permian-Triassic boundary (Botha and Smith, 2006;Day et al, 2015;Gastaldo et al, 2015;Rubidge et al, 2013;Smith and Botha, 2005;Smith and Botha-Brink, 2014;Smith and Ward, 2001;Ward et al, 2005). The excellent preservation of the associated vertebrate assemblages has led to a large library of published faunal information, complemented by palynological data, that has been extrapolated globally to understand the patterns of tetrapod extinctions and their timing relative to the end-Permian marine extinction at ca.…”
Section: Introductionmentioning
confidence: 99%
“…However, this correlation is complicated by the discovery at Serra do Cadeado of a tapinocephalid dinocephalian (Boos et al, 2015), which is a clade largely thought to occur only in the Guadalupian. The discovery of an Endothiodon species in likely Guadalupian strata in Tanzania (Angielczyk et al, 2014a;Cox and Angielczyk, 2015) and radiometric dates from the Karoo Basin suggest that the lower Pristerognathus zone is Guadalupian in age (Day et al, 2015). These issues raise questions about the Lopingian age assignment of the tetrapod-bearing horizons, given that they would imply the existence of a late-surviving dinocephalian, and also whether the localities sample a single fauna.…”
Section: Brazilmentioning
confidence: 93%
“…Correlations among these localities, and to strata in other basins, are obscure because of uncertainties in the exact stratigraphic relationships of the individual fossiliferous outcrops, and the fact that they preserve largely distinct faunal assemblages that include taxa with contradictory biostratigraphic implications (see reviews in Boos et al, 2013Boos et al, , 2015. The Serra do Cadeado localities frequently have been considered to be Lopingian in age, based on the presence of the dicynodont Endothiodon (Barberena et al, 1985;Langer, 2000;Cisneros et al, 2005;Dias-daSilva, 2012;Boos et al, 2013), which is found in the Lopingian Pristerognathus, Tropidostoma, and Cistecephalus Assemblage Zones of the Karoo Basin (e.g., Smith et al, 2012;Day et al, 2015). However, this correlation is complicated by the discovery at Serra do Cadeado of a tapinocephalid dinocephalian (Boos et al, 2015), which is a clade largely thought to occur only in the Guadalupian.…”
Section: Brazilmentioning
confidence: 99%
See 1 more Smart Citation